On the occurrence of Varanus nebulosus (Gray, 1831) (Squamata: Varanidae) on Riau Archipelago, Indonesia - Arida, Evy; Setyawatiningsih, Sri Catur (Zootaxa, 2015)
The occurrence of Varanus nebulosus (Gray, 1831) on Sumatra still remains open for debates, while records are limited, especially those associated with a voucher specimen. The oldest record of V. nebulosus that is associated with a specimen, i.e. SMF 11554 is dated back to 1889 and presumably from Bengal (“Bengalen”), which now lies around Bangladesh. The specimen is kept at Senckenberg Museum Frankfurt (SMF) in Germany. We collected specimens from two islands in the Riau Archipelago, just west of Sumatra and provided new distribution data for this protected species of Monitor lizard in Indonesia. The two recent records represent populations of V. nebulosus other than those already known in the literature and are among the closest known occurrences to Sumatra. We suggest that islands in the Riau Archipelago might have been the stepping stones for a historical dispersal of this species from mainland Southeast Asia and Singapore.